2022
DOI: 10.3390/foods11131976
|View full text |Cite
|
Sign up to set email alerts
|

Origin and Fate of Acrolein in Foods

Abstract: Acrolein is a highly toxic agent that may promote the occurrence and development of various diseases. Acrolein is pervasive in all kinds of foods, and dietary intake is one of the main routes of human exposure to acrolein. Considering that acrolein is substantially eliminated after its formation during food processing and re-exposed in the human body after ingestion and metabolism, the origin and fate of acrolein must be traced in food. Focusing on molecular mechanisms, this review introduces the formation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 146 publications
(145 reference statements)
1
26
0
Order By: Relevance
“…The Ser-sourced 5-formyl-3-methylene-3,6-dihydropyridin occurred in high amounts in all foods, and up to 880.3 μg/kg was detected in biscuits. The contents of interaction products were much higher than those of free ACR and FA, such as ACR in potato crisps (16.3–23.3 μg/kg) . Moreover, their content is also higher than that of the amino acid–ACR adduct by 4-fold and 7–16-fold than alanine- and serine-sourced adducts as we previously reported .…”
Section: Resultssupporting
confidence: 63%
See 2 more Smart Citations
“…The Ser-sourced 5-formyl-3-methylene-3,6-dihydropyridin occurred in high amounts in all foods, and up to 880.3 μg/kg was detected in biscuits. The contents of interaction products were much higher than those of free ACR and FA, such as ACR in potato crisps (16.3–23.3 μg/kg) . Moreover, their content is also higher than that of the amino acid–ACR adduct by 4-fold and 7–16-fold than alanine- and serine-sourced adducts as we previously reported .…”
Section: Resultssupporting
confidence: 63%
“…In addition, microorganisms used for food fermentation produce ACR from glycerol catalyzed by glycerol/diol dehydratase . In processed foods, especially in thermally processed ones, ACR is generated through the degradation of carbohydrate and methionine, lipid oxidation of polysaturated fatty acids in edible oils, and dehydration of glycerol released from oils. , As a result, ACR is present in almost all kinds of foods, including cheese, beer, fried foods, fruits, vegetables, and codfish fillet. Up to 1000, 11,100, and 198,100 μg/L (kg) ACR have been reported in cheese, whiskey, and frying oils, respectively .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Acrolein was present in heated vegetable oils, and the amount of acrolein could be 10 times higher after reheating [ 11 ]. Heating oil could reduce the cis-double bond content of triglycerides and increase the formation of trans unsaturated aldehydes such as acrolein [ 12 ]. Furthermore, there were studies that identified the thermal synthesis of acrolein from glucose.…”
Section: Acrolein Sources and Toxicokineticsmentioning
confidence: 99%
“…The toxicity of acrolein alone has been well-studied. The World Health Organization has classified acrolein as a class 2A carcinogen, and established a provisional tolerable oral acrolein intake of 7.5 μg kg −1 bw day −1 for non-neoplastic effects [ 54 ]. Acrolein produced by GDH-competent intestinal bacteria by metabolizing glycerol can lead to the formation of the acrolein-DNA adduct, which may induce mutations in a model system containing resting cells of L. reuteri in combination with calf thymus DNA or bovine serum albumin.…”
Section: Toxicity Of the Reuterin Systemmentioning
confidence: 99%